Peer Engagement Behaviors: Conceptualization and Research Directions. (November 2019) - Lin, Meizhen; Miao, Li; Wei, Wei; Moon, Hyoungeun
Using social network theory as a theoretical root, this study introduces the concept of peer engagement behaviors and discusses its characteristics in relation to customer, employee, and actor engagement behaviors. This study identifies several sets of foundational research questions related to peer engagement behaviors that focus on unique attributes such as role duality, role fluidity, platform centrality, tie strength, and multidirectionality of peer engagement behaviors. Directions for broad areas of future research are also discussed to encourage theory-building on topics related to measurement, classification, subjective experiences, antecedents, and consequences of peer engagement behaviors.